Analysis of human gait asymmetry using wearable ultrasonic sensors - Zhao, Shan (2017)
This report proposes the analysis of a gait asymmetry system using wireless wearable ultrasonic sensors, which can be used in rehabilitation process. Gait asymmetry in elderly occurs in various medical and pathological conditions such as chronic stroke and Parkinson’s diseases. The proposed ultrasonic system enables wireless communication between an ultrasound transmitter (mobile) and multiple receivers (anchors) placed at known positions. The gait movement was obtained from the mobile placed on the subject’s ankle by using spherical positioning technique. A controller (Arduino) was used in wireless communication between a personal computer (PC) and ultrasonic sensors in the gait asymmetry detection system. Walking experiments conducted with two healthy subjects at allowed us to observe the performance on gait asymmetry system. The results of experiment validated against a camera-based tracking system. These results proved that wearable ultrasonic sensor system will be working well in rehabilitations and sports.